2022
DOI: 10.3389/fped.2022.995167
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Myocarditis with nonsustained ventricular tachycardia following COVID-19 mRNA vaccination in a female adolescent

Abstract: Children with underlying medical conditions potentially develop severe illness from Coronavirus disease 2019 (COVID-19). The use of vaccines against COVID-19 is currently recommended for the pediatric population. The COVID-19 vaccine has a temporal association with the occurrence of myocarditis. Although most patients with COVID-19 vaccination-associated myocarditis (C-VAM) exhibit a mild clinical course and rapid recovery, C-VAM potentially causes electrical instability and sudden cardiac death. Herein, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Some cases of cardiac arrhythmias, including non-sustained ventricular tachycardia [ 86 ], atrial fibrillation [ 87 ], high-degree atrioventricular block [ 88 ], have also been described without previous clinical signs of myocarditis; however, these observations were made without definitely ruling out any myocardial injury by using cardiac MRI. A large study enrolling 7934 high school students after mRNA vaccination and ECG screening revealed that the second dose of anti-SARS-CoV-2 vaccination with a mRNA-based vaccine can have significant cardiac adverse effects.…”
Section: Covid-19 Vaccination-associated Arrhythmiasmentioning
confidence: 99%
“…Some cases of cardiac arrhythmias, including non-sustained ventricular tachycardia [ 86 ], atrial fibrillation [ 87 ], high-degree atrioventricular block [ 88 ], have also been described without previous clinical signs of myocarditis; however, these observations were made without definitely ruling out any myocardial injury by using cardiac MRI. A large study enrolling 7934 high school students after mRNA vaccination and ECG screening revealed that the second dose of anti-SARS-CoV-2 vaccination with a mRNA-based vaccine can have significant cardiac adverse effects.…”
Section: Covid-19 Vaccination-associated Arrhythmiasmentioning
confidence: 99%